COLOURED GILL NETS FOR RESERVOIR FISHING - NARAYANAPPA, G; KHAN, A A; NAIDU, R M (Fishery Technology, 2017)
Experimental fishing with different coloured nets has shown that white net yields better catch. The efficiency of the coloured nets was in the order yellow, grey, green and blue. Though there is little evidence to show some species preference to a particular colour, the results wne not conclusive as the analysis of variance indicated that interaction between species and colour is significant only at 5% level.